The joint effect of gestational diabetes mellitus and hypertension contribute to higher risk of diabetes mellitus after delivery: a nationwide population-based study - Ho-Poh Kek; Yu-Tsun Su; Shu-Jiin Tey; Ming-Chun Yang; Li-Ching Chang; Yun-Hsiang Hung; Ching-Chung Tsai (BMC, 2023)
Abstract Background Gestational diabetes mellitus (GDM) and pregnancy-induced hypertension (PIH) are known risk factors for postpartum diabetes mellitus (DM) and hypertension, respectively. This study aimed to examine the association between the co-occurrence of GDM and PIH and the subsequent development of diabetes mellitus (DM), hypertension, and metabolic syndrome. Methods A cohort study was conducted using data from the Taiwan National Health Insurance Research Database (TNHIRD). The study population included 2,297,613 pregnant women with no history of certain medical conditions who gave birth between 2004 and 2015. The women were classified into four cohorts based on their medical history: GDM cohort, PIH cohort, both GDM and PIH cohort, and normal cohort (without GDM and PIH). Results The GDM cohort had a higher risk of developing DM, hypertension, and metabolic syndrome than the normal cohort, with hazard ratios of 7.07, 1.54, and 2.51, respectively. The PIH cohort also had an increased risk for these conditions compared with the normal cohort, with hazard ratios of 3.41, 7.26, and 2.68, respectively. The cohort with both GDM and PIH had the highest risk of developing postpartum DM, hypertension, and metabolic syndrome, with hazard ratios of 21.47, 8.02, and 5.04, respectively, compared with the normal cohort. Conclusion The cohort of patients with both GDM and PIH had the highest impact on developing postpartum DM compared with either condition alone cohort. Furthermore, the co-occurrence of both conditions increases the risk, with a higher likelihood of developing postpartum DM than hypertension or metabolic syndrome.